ANALYSIS OF HEALTH SERVICE QUALITY AND PATIENT SATISFACTION OF BAREBBO PRIMARY HEALTHCARE BONE REGENCY - A. Ulfiana Fitri; Meliana Handayani (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
Quality health services are an important factor in achieving patient satisfaction. Patient satisfaction is the level of patient feelings that arise as a result of the performance of the health services they receive after the patient compares them with what they expected. Satisfaction is the level of feelings experienced by the patient as a result of the provision of health services received by the patient after comparing it with his expectations. Community satisfaction is achieved if the quality of service provided has a good reputation. This research aims to determine and measure the quality of health services at the Barebbo Community Health Center, Kec. Barebbo, Kab. Bone. This research uses quantitative research using objective measurements and statistical analysis of data samples collected through research instruments such as questionnaires. The results of this study indicate that patients at Puskesmas Barebbo, Kec. Barebbo, Kab. Bone are satisfied with the health services provided by health workers at the Puskesmas and all variables are interrelated with patient satisfaction variables at Puskesmas Barebbo, Kec, Barebbo, Kab. Bone. Based on the chi-square test, service quality and patient satisfaction are interconnected between the dependent and independent variables.